Estudo da viabilidade de meios alternativos de preservação e proteção da interface adesivo/dentina - Ferraz, Camila de Ataíde e (2017)
Adhesive/dentin interface is considered the most fragile link of resin composite restorations. The lack of durable and effective dentin adhesives due to failure at adhesive interface is a great concern for resin composite restoration durability. It is relevant to develop researches to test alternatives of preservation and protection of this interface and its influence on bond strength, immediately and overtime. Thus, the present thesis was constituted by three chapters that aimed, respectively: 1) To synthesize and characterize beta-tricalcium phosphate (β-TCP) and to evaluate the interfaces of adhesive systems loaded with β-TCP bioactive particles and dentin; 2) To characterize the bonding interface of β-TCP loaded and diacetate chlorhexidine-loaded adhesive systems, and to evaluate the bond strength of these materials to sound dentin immediate and after one year; and 3) To synthesize and to characterize nano-hydroxyapatite (n-HA) particles using means of different synthetic routes. Three in vitro studies were performed as methodological approaches, described in different chapters. In Chapter 1 and 2, dentinal surface of fifteen healthy human molars were divided into three experimental groups (n = 5). In Chapter 1, was applied to the teeth Adper Single Bond 2 adhesive system (SB) (SB-control); SB 30% w/v of β-TCP1 (40 nm) (SB-β1) or SB 30% w/v of β-TCP2 (23 nm) (SB-β2). In Chapter 2, was applied: SB (Control); SB 30% w/v of β-TCP1 (40 nm) (SB-βTCP) and SB 2% w/v of DA (SB-DA). The teeth were restored and sticks specimens were prepared and submitted to bond strength test after 24 hours and 1 year. Representative specimens from each group were submitted to scanning electron microscopy (SEM) and micro-Raman spectroscopy analysis. The degree of conversion of the adhesives was determined using FTIR. In Chapter 3, three different methods of synthesis of nano-sized hydroxyapatite (n-HA) were tested. In method 1, n-HA was synthesized by immersing silica particles (10-20 nm) in simulated solution of body fluid for 4 weeks, under agitation and at 37°C. In method 2, n-HA was synthesized using (NH4).2HPO4, Ca(NO3)2.4H2O and NH4OH, and the solution was allowed to stand for 10 days at room temperature. In method 3, n-HA was synthesized using H3PO4 and Ca(OH)2, and remained at room temperature for 72 h. DRX, TEM and EDX analyzes were carried out to characterizations. Data were submitted to One-Way ANOVA, 2-Way ANOVA and Scheffe tests (p<0,05). The results showed that it was possible to synthesize β-TCP particles and to incorporate β-TCP into the adhesive system (degree of conversion, p> 0.05), and that such incorporation did not impair the bonding strength, either after 24 h or after 1 year of storage. The microtensile results also pointed to high stability of the adhesives incorporated to β-TCP particles, since the bond strength values after 1 year was higher than those obtained by the control group (p <0.05) (Chapter 1). It was possible to incorporate β-TCP and DA to the adhesive system (degree of conversion, p> 0.05). SEM results and micro-Raman mapping and analysis demonstrated differences in β-TCP and DA distribution at the adhesive interface when incorporated into adhesive systems. For the SB group, the resin tags and the hybrid layer was homogeneously formed. In the SB-DA group, the chlorhexidine particles remained concentrated at the top of the hybrid layer and diffused into the dentinal tubules with the adhesive. At the adhesive interfaces of the SB-βTCP group, bioactive particles did not penetrate the hybrid layer and all of them agglomerated in the adhesive layer. After microtensile test, adhesive strength values were statistically lower for the SB group than for the other SB-DA and SB-βTCP groups (p <0.05) (Chapter 2). It was possible to sinthesize n-HA particles by the three synthetic methods tested. The particles synthesized by the first two methods presented similar X-ray diffraction test peaks pattern to those of the control (commercial n-HA). Concerning the spatial morphological arrangement, the synthesized particles presented a shape similar to prisms, different from the control, which presented a spatial arrangement in the shape of regular spheres and of different sizes (Chapter 3). Therefore, it is concluded that the alternative means of preservation and protection of the adhesive /dentin interface proposed in this work did not impair the physical and mechanical properties of the adhesive systems studied. The incorporation of bioactive particles of β-TCP into adhesive system may be able to preserve bonding stability overtime.